Zebrafish Models of LAMA2-Related Congenital Muscular Dystrophy (MDC1A) - Fabian, Lacramioara; Dowling, James J. (Frontiers in Molecular Neuroscience, 2020)
LAMA2-related congenital muscular dystrophy (CMD), also referred to as merosin deficient CMD (MDC1A), is a severe neonatal onset muscle disease caused by recessive mutations in the LAMA2 gene. LAMA2 encodes laminin 2, a subunit of the extracellular matrix oligomer laminin 211. There are currently no treatments for MDC1A, and there is an incomplete understanding of disease pathogenesis. Zebrafish, due to their high degree of genetic conservation with humans, large clutch sizes, rapid development, and optical clarity, have emerged as an excellent model system for studying rare Mendelian diseases. They are particularly suitable as a model for muscular dystrophy because they contain at least one orthologue to all major human MD genes, have muscle that is similar to human muscle in structure and function, and manifest obvious and easily measured MD related phenotypes. In this review, we present the existing zebrafish models of MDC1A, and discuss their contribution to the understanding of MDC1A pathomechanisms and therapy development.